Pembaharuan Hukum Pidana di Indonesia: Analisis KUHP Baru dan Implikasinya - I Made Kresna Sanjaya Aditama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The reform of criminal law in Indonesia has become an increasingly urgent necessity in line with social developments, technological advancement, and the growing complexity and diversity of crime. Law Number 1 of 2023 concerning the new Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) emerges as a comprehensive effort to replace the colonial-era Criminal Code and to align the national criminal law system with the current conditions of Indonesian society. This new Criminal Code introduces several significant changes, including the regulation of cybercrime, protection of the environment, the reinforcement of humanitarian values, and the strengthening of the principle of limiting criminal sanctions on individual liberty in order to ensure the protection of human rights. This paper aims to analyze the direction and substance of the Criminal Code reform, evaluate its potential implementation, and assess the implications of these changes for criminal law enforcement practices in Indonesia. The research method employed is a literature review using a normative approach, conducted through the analysis of statutory regulations, criminal law theories, and relevant case studies. The results of the analysis indicate that the new Criminal Code provides a more adaptive and responsive legal framework to contemporary issues; however, the effectiveness of its implementation largely depends on the readiness of law enforcement authorities, the intensity of regulatory socialization, and the level of public legal awareness. This study concludes that criminal law reform represents a strategic step toward realizing a criminal justice system that is more just, effective, and aligned with the values of Pancasila.